2012
DOI: 10.1111/j.1468-2338.2012.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Immigration policy and market institutions in liberal market economies

Abstract: This article examines how the regulatory character of market institutions shapes government responses to labour shortages, with particular reference to immigration policy. The period between the late 1990s and the late 2000s saw many advanced economies relax entry controls on select categories of foreign workers. This trend was most pronounced among states with liberal market institutions. The underlying reasons for these trends are analysed through an examination of the motivations for reform in Australia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 53 publications
(49 reference statements)
2
47
1
Order By: Relevance
“…Rhodes indicates that in spite of a diversity of political traditions and systems, there has been a global convergence away from direct government policy administration toward the management of public services by a network of agents, by-passing the state entirely or working in partnership with it. While power to allocate resources (including labour to large public infrastructure projects) was, in the past, the main preserve of government agencies, commercially-driven interests have increasingly assumed this responsibility (Wright 2012). Of Rhodes' analysis, Mette Kjaer notes (2011, 102): "By pointing at the many simultaneous processes of 'hollowing out', Rhodes' analyses demonstrated that the central state was losing steering capacity."…”
Section: Transitions From Government To Network Governancementioning
confidence: 99%
“…Rhodes indicates that in spite of a diversity of political traditions and systems, there has been a global convergence away from direct government policy administration toward the management of public services by a network of agents, by-passing the state entirely or working in partnership with it. While power to allocate resources (including labour to large public infrastructure projects) was, in the past, the main preserve of government agencies, commercially-driven interests have increasingly assumed this responsibility (Wright 2012). Of Rhodes' analysis, Mette Kjaer notes (2011, 102): "By pointing at the many simultaneous processes of 'hollowing out', Rhodes' analyses demonstrated that the central state was losing steering capacity."…”
Section: Transitions From Government To Network Governancementioning
confidence: 99%
“…However, more recently the trend has re moved away from permanent settlement based on colonial and cultural ties, to 'demand-driven' and temporary migration schemes as evident within most OECD countries (Wright 2012) These demand-driven schemes have allowed employers, rather than government or supra-national agencies, to shape the entry and location of migrant workers (Dustmann and Weiss, 2007;Newland and Agunias, 2007;Chaloff and Lemaître, 2009;Standing, 2009;Baubock, 2011). For example, demand-driven schemes operate in the United Kingdom (Tier Two visa), USA (H-1B visa), Canada (Temporary Foreign Worker Program and Canadian Experience Class), Germany (Green card system), Sweden (employer-sponsored worker scheme) as well as Australia (Temporary Skilled 457 visa scheme) (Papademetriou et al, 2008;OECD 2013;Government of Canada, 2014;Emilsson et al, 2014).…”
Section: Skilled and 'Demand-driven' Mobilitymentioning
confidence: 99%
“…For example, demand-driven schemes operate in the United Kingdom (Tier Two visa), USA (H-1B visa), Canada (Temporary Foreign Worker Program and Canadian Experience Class), Germany (Green card system), Sweden (employer-sponsored worker scheme) as well as Australia (Temporary Skilled 457 visa scheme) (Papademetriou et al, 2008;OECD 2013;Government of Canada, 2014;Emilsson et al, 2014). Notwithstanding nation-specific differences, these schemes generally provide migrants with fixed-term visas, which are tie them to specific employers and occupations (McLaughlan and Salt, 2002;Cully, 2011;Wright, 2012;Groutsis et al, 2015).…”
Section: Skilled and 'Demand-driven' Mobilitymentioning
confidence: 99%
“…These include, among other things, the gendered nature of labor markets, employee participation, job quality, vocational training systems, labor immigration policies, collective bargaining and union membership density (Martin and Bamber 2004;Frege and Kelly 2004;Estevez-Abe 2006;Harcourt and Wood 2007;Lansbury and Wailes 2008;Bamber et al 2009;Goergen et al 2012;Wright 2012;Frege and Godard 2014). National institutions still matter, then, and have a continuing impact on strategic choices of ER actors including the form of employment, the determination of pay and other working conditions, and how their interests are represented.…”
Section: National Institutionsmentioning
confidence: 99%